Rivers that become reservoirs: an ethnography of water commodification in Lesotho - Sello, Kefiloe (Environmental Humanities South, 2022)
Through exploring the relationship of people to water and how that relationship changes when water becomes a commodity, this study addresses the devaluation of the relationship of people and water in the environment they live in and contrasts the devaluation with the value attributed to commodified water by neoliberal economic policy. Where the relationships between people and water are financialised, commodification sets people and water apart in planning and policies as if they are separate entities. Focusing on the effects of the Lesotho Highlands Water Project in the commodification of water in Lesotho, this study contrasts life lived with freeflowing water and with commodified water. Through ethnographic data collected over 18 months in three villages around the Katse Dam and the Mohale Dam, the dissertation demonstrates that development agencies do not take into consideration the human-nonhuman relationship that exist between communities and their environment. The study demonstrates that economic development through the damming of rivers has rendered people both ecologically and economically precarious. Drawing from these findings, the study proposes that development based on the extraction of natural resources and the assumption that people and environment are separate, should be replaced with an integrated theory of habitability and wellbeing that includes, in its social theory, the relationships of people with soil and water. The thesis was guided by multispecies, political ecology and economic anthropology theories.